Oral health assessment for users of marijuana and cocaine/crack substances - Mariane Beatriz Sordi; Rachel Captzan Massochin; Alessandra Rodrigues de Camargo; Tadeu Lemos; Etiene de Andrade Munhoz (Sociedade Brasileira de Pesquisa Odontológica, 2017)
Abstract: The objective of this study was to assess the oral health status of users of illicit drugs such as marijuana and cocaine/crack and compare it with individuals not using these chemical substances. Questionnaires were applied to 35 illicit drugs users to gather information on demographic status, general health, and use of drugs. Then, a clinical assessment of the oral health condition was performed to collect data on decayed, missing and filled teeth (DMFT) index, salivary flow rate (SFR), and mucosal lesions. The control group was composed of 35 non-illicit drug users. In the experimental group, 91.43% were males, 80% were smokers, and 42.85% were alcoholics. Cocaine was the most common drug used (77.15%), followed by marijuana (68.6%), and crack (51.4%). The average DMFT index was 9.8 and the SFR was reduced in 60% of subjects. Mucosal alterations were detected, but no potentially malignant disorders or oral cancer were diagnosed. Compared to control group, significantly higher values for gender (40%, p = 0.0001), smoking (22.86%) and heavy drinking (5.7%) habits (p = 0.0001), SFR (31.4%; p = 0.0308), and oral lesions (p = 0.0488) were found for the experimental group, although significantly higher values were found in the control group for DMFT index (p = 0.0148). It can be concluded that the use of illicit drugs contributed to an increased prevalence of oral mucosa lesions. In addition, a decline on SFR and a reduced DMFT index was observed for illicit drug users.